مظفر وارثی کی نعت گوئی کے امتیازات - Awan, Dr. Naseer Ahmad (Zoraiz, 2023)
Muzaffar Warsi is an honorable poet of Urdu poetry after the creation of Pakistan. Although he wrote splendid verses in different forms of poetry such as Ghazal, but his reputation lies in Naat literature, in which he contributed both in thematic and artistic levels and composed Naat literature on modern standards. In this article, the distinctive features of his Naat literature have been discussed. He benefited from tradition but his individuality lies in novelty. He made diverse topics splendid by presenting them in different styles, eye-catching rhymes and meters. On the basis of this diversity, his Naats are considered distinctive from the Naats of most of his contemporary poets. The researchers and the critics have acknowledged his unique qualities and paid him tribute.